Search for charged Higgs bosons decaying via H-+/- -> tau nu in t(t)over-bar events using pp collision data at root s=7 TeV with the ATLAS detector - Onofre, A. (2012)
The results of a search for charged Higgs bosons are presented. The analysis is based on 4.6fb−1 of proton-proton collision data at s√=7TeV collected by the ATLAS experiment at the Large Hadron Collider, using top quark pair events with a τ lepton in the final state. The data are consistent with the expected background from Standard Model processes. Assuming that the branching ratio of the charged Higgs boson to a τ lepton and a neutrino is 100 %, this leads to upper limits on the branching ratio of top quark decays to abquarkandachargedHiggsbosonbetween5%and1%forchargedHiggsbosonmasses ranging from 90 GeV to 160 GeV, respectively. In the context of the mmaxh scenario of the MSSM, tan β above 12-26, as well as between 1 and 2-6, can be excluded for charged Higgs boson masses between 90 GeV and 150 GeV.